Simulation of Hydraulic Fracture Failure in Concrete Gravity Dams Under Different Loads - WANG Yang; SUN Jinshan; WANG Gaohui; ZHENG Jiawei; LI Yongzhen (Renmin Zhujiang)
This study investigated the problem of hydraulic fracture propagation in concrete gravity dams. A fracture mechanics model for concrete was constructed, and cohesive force units were used to simulate the propagation of fractures. Methods for calculating water pressure within the hydraulic fractures under static and dynamic conditions were established. The propagation process of fractures in gravity dams under the effects of hydrostatic pressure, seismic loads, and underwater explosion loads was simulated respectively. The results indicate that the hydraulic fracture calculation model for concrete gravity dams proposed in this paper has a good simulation effect on the distribution and propagation of fractures under the effects of hydrostatic pressure, seismic loads, and underwater explosion loads, which is close to the results of reference literature. Under the action of hydrostatic pressure, the propagation length of fractures in the gravity dam is positively correlated with the water head height; under the action of seismic loads, the water pressure inside the fractures significantly promotes the propagation length of the fractures; under the action of underwater explosion loads, the shock wave first causes extensive damage to the upstream dam face and then expands downward and concentrates in the middle and heel of the dam. The research results provide a basis for the stability analysis of hydraulic fractures in concrete gravity dams and have important reference values for fracture control and dam safety management in practical dam engineering.